Politik Identitas Dan Representasi Politik (Studi Kasus pada Pilkada DKI Periode 2018-2022) - Nasrudin, Juhana (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2018)
Identity and representation are two significant things in human life. While religion and ethnicity are two things that become identity and representation of humans. The democratic process in Indonesia is inseparable from the orientation of identity politics and representation. This research is qualitative in nature which focuses on research in the case of the second round of DKI regional elections in the period 2018-2022. The case will be analyzed using the theory of identity politics and political representation. The results of the study indicate that the orientation of identity politics and political representation influences the democratic process in the case of the 2018-2022 DKI elections.